2006
DOI: 10.1213/01.ane.0000226140.84281.3e
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Improves Survival in Burn Injury Followed by Sepsis in Rats

Abstract: Ketamine was reported to decrease cytokine production and improve survival after Escherichia coli-induced sepsis. We examined whether ketamine decreased interleukin (IL)-6 production and improved survival after 1) burn injury or 2) burn injury combined with sepsis (E. coli) at 24 h. Ketamine (10 mg/kg) or saline was given at 1 h after burn injury (G 1, 2, 5, 6), 24 h after burn injury (G 3, 4), or at E. coli inoculation (G 7, 8). Mortality was recorded for 7 days and IL-6 was measured in serum at 6 h after bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 23 publications
2
25
0
5
Order By: Relevance
“…It also has been demonstrated that ketamine could improve survival in burn injury followed by sepsis in rats (33). In the present study, we found that ketamine at the doses of 5 mg/kg and 10 mg/kg could improve survival in a CLP model of sepsis.…”
Section: Discussionsupporting
confidence: 71%
“…It also has been demonstrated that ketamine could improve survival in burn injury followed by sepsis in rats (33). In the present study, we found that ketamine at the doses of 5 mg/kg and 10 mg/kg could improve survival in a CLP model of sepsis.…”
Section: Discussionsupporting
confidence: 71%
“…Patients were excluded, if they met one of the following criteria: age !75 yr, recent (,14 days) myocardial infarction, unstable angina with elevated creatine kinase-MB (CK-MB), elevated serum creatinine (.1.3 mg dl 21 ) before operation, left ventricular ejection fraction (LVEF) ,40%, previous cardiac surgery, previous stroke or pulmonary disease, and history of treatment with steroid or non-steroidal anti-inflammatory drugs within a month. Emergency operations were also excluded.…”
mentioning
confidence: 99%
“…Using a computer-generated randomization method, patients were randomly assigned to receive either a bolus of ketamine 0.5 mg kg 21 (Ketamine group, n¼25) or normal saline (Control group, n¼25) during induction of anaesthesia. Being a double-blinded study, patients, anaesthetic provider, and anaesthetist collecting data were blinded to the study group, and ketamine or normal saline was prepared by an independent researcher in equal volumes in 10 ml syringes.…”
mentioning
confidence: 99%
“…Ketamine may exert beneficial anti-inflammatory effects in patients with burns and or sepsis. [70][71][72] Ketamine may be the agent of choice if one wishes to avoid manipulation of the airway (e.g., after placement of fresh facial grafts, for splint or dressing removal, for brief procedures such as dressing or line changes, insertion of Foley catheters in pediatric patients or for patients with toxic epidermal necrolysis syndrome). 73 The addition of benzodiazepines is often recommended to reduce the incidence of dysphoria.…”
Section: Opioidsmentioning
confidence: 99%